2015
DOI: 10.1016/j.semcancer.2015.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Sustained proliferation in cancer: Mechanisms and novel therapeutic targets

Abstract: Proliferation is an important part of cancer development and progression. This is manifest by altered expression and/or activity of cell cycle related proteins. Constitutive activation of many signal transduction pathways also stimulates cell growth. Early steps in tumor development are associated with a fibrogenic response and the development of a hypoxic environment which favors the survival and proliferation of cancer stem cells. Part of the survival strategy of cancer stem cells may manifested by alteratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
371
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 540 publications
(408 citation statements)
references
References 687 publications
4
371
0
4
Order By: Relevance
“…The dysregulation of cell proliferation is one of the causative factors of bladder cancer (23,24). In the present study, the One Solution Cell Proliferation assay and colony formation assay demonstrated that GAPLINC knockdown significantly inhibited the proliferation of UM-UC-3 and T24 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The dysregulation of cell proliferation is one of the causative factors of bladder cancer (23,24). In the present study, the One Solution Cell Proliferation assay and colony formation assay demonstrated that GAPLINC knockdown significantly inhibited the proliferation of UM-UC-3 and T24 cells.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] [13][14][15][16][17][18] The miRNAs regulated by a selection of important anticancer natural products and compounds that obtained from main known medicinal plants are presented in Table 1. As summarized in Table 1, recent studies and clinical trials which are aimed to find novel targets for the treatment of multiple types of cancers, have emphasized the importance of the consumption of natural agents-rich diet, including curcumin, berberine, alkaloids, mitomycin C, resveratrol, camptothecin, topotecan, trabectedin, matrine, honokiol, isoflovones, indole-3-carbinol, sulforaphane, water soluble vitamins, diallyl disulfide, 3,3'-diindolylmethane, epigallocatechin-3-gallate and hesperidin, etc., additionally syntheses of natural products by the liposome or nanoparticle formulations assays.…”
Section: Regulation Of Micrornas Expressions By Dietary Compounds Andmentioning
confidence: 99%
“…As summarized in Table 1, recent studies and clinical trials which are aimed to find novel targets for the treatment of multiple types of cancers, have emphasized the importance of the consumption of natural agents-rich diet, including curcumin, berberine, alkaloids, mitomycin C, resveratrol, camptothecin, topotecan, trabectedin, matrine, honokiol, isoflovones, indole-3-carbinol, sulforaphane, water soluble vitamins, diallyl disulfide, 3,3'-diindolylmethane, epigallocatechin-3-gallate and hesperidin, etc., additionally syntheses of natural products by the liposome or nanoparticle formulations assays. 5,7,[16][17][18] The bioactive compounds and natural products have significant influences on the epigenetic changes in the cancer cells. For instance, they regulate the expression levels of miRNAs by effecting the several proteins that are involved in the stages of tumorogenesis both cancer initiation and development.…”
Section: Regulation Of Micrornas Expressions By Dietary Compounds Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Curcuma longa is a herbaceous plant that the rhizome is widely used to flavor and color in foods [1]. It is a dietary source of curcuminoid compounds included curcumin (75 -95%), dimethoxycurcumin and bisdimethoxy-curcumin.…”
Section: Introductionmentioning
confidence: 99%